(untitled) (Proceedings of the Global Public Health Conference, 2018)
Mercury (Hg) is a natural element that can be found in air, water and soil. However, various activities may increase mercury levels including artisanal and small-scale gold mining (ASGM) activities. Mercury is toxic and persistent that it can harm humans and the environment. The use of mercury in ASGM process can have negative effects on gold miners, one of which is mercury poisoning. Therefore, it is important to know what factors are related with the occurrence of mercury poisoning on gold miners at ASGM. Beside that, there are many studies on mercury poisoning in Indonesia. This research is a systematic review of 5 eligible research journals conducted in the year 2000-2017 in Indonesia. Journals are obtained from Science Direct, Google Scholar and Portal Garuda databases. Factors that are often researched in these studies are age, nutritional status, working hours per day, working frequency per week, working period (years), mercury levels used per day, the use of Personal Protective Equipment (PPE), and fish consumption. Based on a systematic study, most journal finds that the hours worked per day, working frequency per week, working period (years), and the use of PPE are significantly related to mercury poisoning. While, age, nutritional status, mercury levels used per day, and fish consumption have no statistically significant relationship with the occurrence of mercury poisoning on gold miners at ASGM in Indonesia.